Removal of soil biota alters soil feedback effects on plant growth and defense chemistry. Issue 3 (17th October 2018) - Wang, Minggang; Ruan, Weibin; Kostenko, Olga; Carvalho, Sabrina; Hannula, S. Emilia; Mulder, Patrick P. J.; Bu, Fengjiao; van der Putten, Wim H.; Bezemer, T. Martijn
Summary: We examined how the removal of soil biota affects plant–soil feedback (PSF) and defense chemistry of Jacobaea vulgaris, an outbreak plant species in Europe containing the defense compounds pyrrolizidine alkaloids (PAs). Macrofauna and mesofauna, as well as fungi and bacteria, were removed size selectively from unplanted soil or soil planted with J. vulgaris exposed or not to above‐ or belowground insect herbivores. Wet‐sieved fractions, using 1000‐, 20‐, 5‐ and 0.2‐μm mesh sizes, were added to sterilized soil and new plants were grown. Sieving treatments were verified by molecular analysis of the inocula. In the feedback phase, plant biomass was lowest in soils with 1000‐ and 20‐μm inocula, and soils conditioned with plants gave more negative feedback than without plants. Remarkably, part of this negative PSF effect remained present in the 0.2‐μm inoculum where no bacteria were present. PA concentration and composition of plants with 1000‐ or 20‐μm inocula differed from those with 5‐ or 0.2‐μm inocula, but only if soils had been conditioned by undamaged plants or plants damaged by aboveground herbivores. These effects correlated with leaf hyperspectral reflectance. We conclude that size‐selective removal of soil biota altered PSFs, but that these PSFs were also influenced by herbivory during the conditioning phase.